CLINICAL AND IMMUNOLOGICAL FEATURES OF VARIOUS FORMS OF GLOMERULONEPHRITIS - Eshbekov M. A. (Modern American Journals, 2025)
Background. Glomerulonephritis is characterized by marked clinical heterogeneity, largely determined by dysregulation of cytokine-mediated immune responses
Keywords: Glomerulonephritis, cytokines, IL-1β, IFN-γ, immune inflammation, clinical forms.